Glutathione Peroxidase-1 Overexpression Inhibits Transcription of Regenerating Islet-Derived Protein-2 in Pancreatic Islets of Mice (OR11-07-19). (13th June 2019) - Yun, Jun-Won; Zhao, Zeping; Yan, Xi; Vatamaniuk, Marko; Lei, Xin Gen
Abstract: Objectives: We discovered a diminished expression of regenerating islet-derived protein 2 (REG2) in pancreatic islets of glutathione peroxidase-1 (GPX1) overexpressing (OE) mice. This research was to reveal underlying mechanisms for the suppression of Reg2 expression by GPX1 as a major scavenger of reactive oxygen species. Methods: The OE and wild-type (WT) mice and(or) their islets were treated with ROS-generating diquat, streptozotocin, and H2 O2 and ROS-scavenging ebselen and N- acetylcysteine (NAC). Responses of REG2 mRNA and protein levels in the pancreas or islets to these treatments were determined. Thereafter, 13 transcriptional factors (TFs) with putative binding sites in the Reg2 proximate promoter was identified, and their mRNA and protein levels were analyzed in the OE and WT islets treated with ebselen, NAC, and H2 O2 . Chromatin immunoprecipitation of OE and WT islets and sub-sequential deletions of the binding sites in insulin secreting bTC-3 cells were performed to reveal the binding of TFs to the Reg2 promoter and the inhibition of the Reg2 promoter activation by ebselen. Results: Pancreatic and islet REG2 protein production and(or) secretion were positively correlated ( P < 0.05) with the intracellular ROS status. Among the 13 TFs, only activator protein-1 (AP-1) and albumin D box-binding protein (DBP) mRNA and protein levels were elevated ( P < 0.05) in the OE pancreatic islets compared with the WT islets. Their mRNA abundances in the cultured islets were elevated ( P < 0.05) by ebselen and NAC, but decreased ( P < 0.05) by H2 O2 . These responses were contrary to those of Reg2 expression. The two TFs bound to the Reg2 promoter at the location of −168 to 0 base pair (bp). Deleting the AP-1 (−143/−137 and −60/−57 bp) and(or) DBP (−35/−29 bp) binding domains in the Reg2 promoter attenuated and(or) abolished the inhibition of Reg2 promoter activation by ebselen. Conclusions: The diminished Reg2 expression in the GPX1-overproducing pancreatic islets was mediated by a transcriptional inhibition of the gene through two ROS-responsive transcriptional factors, AP-1 and DBP. Our findings revealed GPX1 as a novel regulator of Reg2 expression. Linking these two previously-unrelated proteins will have broad biomedical implications. Funding Sources: This research was supported in part by a NIH grant DK 53, 018.